COVID-19 Pandemic as a Factor for the Paradigm Shift in International Communications. Book Review of ‘Pandémie médiatique. Com de crise/crise de com’ by S. Fouks - T. Yu. Lebedeva; L. V. Minaeva; A. D. Krivonosov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The review examines a new book ‘Media pandemic. Crisis communication / communication crisis’ (‘Pandémie médiatique. Com de crise / crise de com’) by the executive vice-president of the Havas Group Stephan Fouks, which was published in the midst of the COVID-19 pandemic. Building on his rich and unique practical experience as a head of a large media organization, a consultant at international organizations and a presidential campaign manager, the author assesses the role of media communications in the context of the coronavirus outbreak. The book under review is addressed primarily to experts in International Relations. It covers a wide range of issues including the causes of the crisis, which led to a paradigm shift in international communications, and specifi cs of the communication policies in France and some other European states. The author concludes that these policies refl ect a general crisis of the ruling elites (political establishment). Here the author continues to further elaborate on the ideas of his previous book — ‘The New Elites: portrait of a generation that will ignore’ (‘Les Nouvelles Elites: portrait d’une génération 1ui s’ignore’).The author provides a critical analysis of the key elements of communication strategies during the COVID-19 pandemic, from the ruling elites to the expert community, and delineates methods and the role of international communication in the future. The reviewers emphasize that the monograph by Stefan Fouks goes beyond the traditional formats of communication studies, which tended to focus either on the various crises, or on the organization of media structures in diff erent states, public-private partnership, and corporate communications, and thus were too narrow in scope. In ‘Media-pandemic’ the author stresses multidimensional nature of international communications and argues that their paradigmatic shift was brought by both the development of digital technologies and anthropogenic factors in the form of the global COVID-19 pandemic.